The Contribution of Islamic Scholars in Addressing Earthquake and Tsunami (The Study of Malay Minangkabau Manuscripts) - Firdaus Firdaus (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
The aim of this paper is to examine the contribution of Minangkabau muslim scholars in responding to the earthquake and tsunami based on the manuscript of earthquake takwil. The manuscript of the earthquake takwil becomes the window to see how great the contribution of muslim scholars in addressing the natural phenomenon in Minangkabau particularly earthquake and tsunami. In term of natural disaster, this study has been interestingly discussed since the deadly earthquake and tsunami of 26 December 2004 hit Aceh which killed more than 280.000 people. People become traumatized and feared especially the people who live in the areas affected by the earthquake and tsunami. In addition, Indonesia is prone to earthquakes and tsunamis because it lies on the “Ring of Fire”—the line of frequent quakes and volcanic eruptions that circles virtually the entire Pacific rim. The paper looks at problems: (1) Why are people traumatized and afraid in facing earthquakes and tsunamis? (2) Why are the younger generations not asking muslim scholars about the causes and effects of the earthquake and tsunami? Applying philological, historical, social and educational approaches, this article argues that the manuscript of the earthquake takwil as the evidence that people need muslim scholars in explaining natural disaster. muslim scholars teach the students in surau about the cause of the earthquake and its takwil. Earthquakes and tsunamis have long been studied by Minangkabau muslim scholars. Therefore, it needs attention and reinforcement of knowledge for Muslim scholars of West Sumatra now in accordance with the times in addressing natural phenomena such as earthquakes and tsunamis.DOI: 10.15408/insaniyat.v2i1.6587